Eco-Theology-Based Al-Islam and Kemuhammadiyahan Teaching Materials: A Mixed-Methods Needs Analysis at Universitas Muhammadiyah Mataram - Arifin, M. Anugrah; Maimun, Maimun; Abdullah Acim, Subhan; Wildan, Wildan (Jurnal Pendidikan Islam, 2026)
Purpose – This study analyzes the need for eco-theology-based Al-Islam and Kemuhammadiyahan (AIK) teaching materials and identifies gaps in existing materials and stakeholder expectations at Universitas Muhammadiyah Mataram (UMMAT), which is located in disaster-prone West Nusa Tenggara.Design/methods/approach – The study reports the Analysis stage of an ADDIE-based research and development project using a convergent parallel mixed-methods design. Data comprised a systematic literature review of 115 records, of which 22 manuscripts were included; an analysis of a 14-meeting Semester Learning Plan and four AIK textbooks covering 28 chapters; a questionnaire completed by 106 students; interviews with seven stakeholders; and observations of three AIK sessions totalling 270 minutes.Findings – None of the 22 reviewed manuscripts provided a dedicated  eco-theology-based AIK textbook for Muhammadiyah higher education. All four existing textbooks lacked explicit eco-theology content, interconnection with students’ disciplines, environmental examples, and related exercises. Classroom observations found no explicit use of eco-theological Qur’anic verses orteaching materials and only one student-initiated environmental question. The four questionnaire items directly measuring need recorded means of 4.26–4.47 ona five-point scale.Research Implications – The findings provide requirements for proceeding to the Design and Development stages of contextual AIK teaching materials that retain core AIK content while integrating Islamic ecological responsibility.